1936
DOI: 10.1136/bmj.2.3943.218
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hallux Valgus and Rigidus

Abstract: Hallux valgus is met with more frequently than any other deformity of the adult foot. It is seen very occasionally in infants or children as a congenital deformity, but in the vast majority of instances it results directly from the long-continued deforming pressure of badly constructed shoes. Consequently it is found most commonly in women on account of the height of the heel and the narrowness of the toe in the so-called " smart " shoes which they usually wear, and as a rule the full development of the deform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1951
1951
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Several risk factors have been proposed in the literature, including female sex, [14] history of trauma, [15] rheumatoid arthritis,[16] long proximal phalanx of the hallux, [17] varus deformities of the forefoot or rearfoot, [17] HV deformity,[18] soft-tissue contracture, [19] short or long rst metatarsal, [20] increased interphalangeal angle of the hallux, [21] family history, [14] and ill-tting footwear. [22] However, none of these risk factors were determined from epidemiological studies of local residents.…”
Section: Discussionmentioning
confidence: 99%
“…Several risk factors have been proposed in the literature, including female sex, [14] history of trauma, [15] rheumatoid arthritis,[16] long proximal phalanx of the hallux, [17] varus deformities of the forefoot or rearfoot, [17] HV deformity,[18] soft-tissue contracture, [19] short or long rst metatarsal, [20] increased interphalangeal angle of the hallux, [21] family history, [14] and ill-tting footwear. [22] However, none of these risk factors were determined from epidemiological studies of local residents.…”
Section: Discussionmentioning
confidence: 99%
“…A summary of all measured CT parameters is given in Table 2. The average first metatarsal declination angle was 20.1 (range, [16][17][18][19][20][21][22][23][24][25] degrees in the hallux rigidus group and 25.0 (range, 19-30) degrees in the control group. The average second metatarsal declination angle was 24.8 (range, 19-30) degrees in the hallux rigidus group and 27.0 (range, 21-36) degrees in the control group.…”
Section: Ct Assessment Of Hallux Rigidus Foot Alignmentmentioning
confidence: 99%
“…20 These factors include trauma, osteochondritis dissecans, and anatomical abnormalities such as pes planus, forefoot pronation, a long first ray, a tight gastrocnemius, 19 or metatarsus primus elevatus. 1,4,9,12,18,21,22,24…”
mentioning
confidence: 99%
“…The first metatarsophalangeal joint is subject to increased mechanical stress if the great toe or the first metatarsal are longer than the second ray. A number of authors have reported an increased incidence of hallux rigidus in patients with a long great toe or with a long first metatarsal [10,11,15,18,37–39], but no statistical correlation has been proven. Infection or metabolic and inflammatory joint disease may affect the first metatarsophalangeal joint and result in painful limitation of motion and in degenerative arthritis.…”
Section: Aetiologymentioning
confidence: 99%
“…In view of a recurrence rate of up to 80%[42], this technique can not generally be recommended. Subcapital dorsiflexion osteotomy of the first metatarsal has also been recommended [38,43–45], but this is technically more difficult than cheilectomy or osteotomy of the proximal phalanx.…”
Section: Surgical Treatment Of Hallux Rigidusmentioning
confidence: 99%